Potential Mechanisms Underlying the Role of Coffee in Liver Health - Alferink, Louise J. M.; Kiefte-de Jong, Jessica C.; Darwish Murad, Sarwa (Seminars in Liver Disease, 2018)
Coffee, the most consumed hot beverage worldwide, is composed of many substances, of which polyphenols, caffeine, and diterpenoids are well studied. Evidence on potential effects of coffee on human health has been accumulating over the past decades. Specifically, coffee has been postulated to be hepatoprotective in several epidemiological and clinical studies. Several underlying molecular mechanisms as to why coffee influences liver health have been proposed. In this review, the authors summarized the evidence on potential mechanisms by which coffee affects liver steatosis, fibrosis, and hepatic carcinogenesis. The experimental models reviewed almost unanimously supported the theorem that coffee indeed may benefit the liver. Either whole coffee or its specific compounds appeared to decrease fatty acid synthesis (involved in steatogenesis), hepatic stellate activation (involved in fibrogenesis), and hepatic inflammation. Moreover, coffee was found to induce apoptosis and increased hepatic antioxidant capacity, which are involved in carcinogenesis.
Keywords: coffee; polyphenols; diterpenoids; caffeine; liver steatosis; fibrosis; hepatocellular carcinoma